Ceramic Primer Heat-Treatment Effect on Resin Cement/Y-TZP Bond Strength - Silva, L. H.; Costa, A. K. F. [UNESP]; Queiroz, J. R. C.; Bottino, M. A. [UNESP]; Valandro, L. F. (Operative Dentistry Inc, 2012)
The purpose of this study was to evaluate the effect of different heat-treatment strategies for a ceramic primer on the shear bond strength of a 10-methacryloyloxydecyl-dihydrogen-phosphate (MDP)-based resin cement to a yttrium-stabilized tetragonal zirconia polycrystal (Y-TZP) ceramic. Specimens measuring 4.5 x 3.5 x 4.5 mm(3) were produced from Y-TZP presintered cubes and embedded in polymethyl methacrylate (PMMA). Following finishing, the specimens were cleaned using an ultrasound device and distilled water and randomly divided into 10 experimental groups (n=14) according to the heat treatment of the ceramic primer and aging condition. The strategies used for the experimental groups were: GC (control), without primer; G20, primer application at ambient temperature (20 degrees C); G45, primer application + heat treatment at 45 degrees C; G79, primer application + heat treatment at 79 degrees C; and G100, primer application + heat treatment at 100 degrees C. The specimens from the aging groups were submitted to thermal cycling (6000 cycles, 5 degrees C/55 degrees C, 30 seconds per bath) after 24 hours. A cylinder of MDP-based resin cement (2.4 mm in diameter) was constructed on the ceramic surface of the specimens of each experimental group and stored for 24 hours at 37 degrees C. The specimens were submitted to a shear bond strength test (n=14). Thermal gravimetric analysis was performed on the ceramic primer. The data obtained were statistically analyzed by two-way analysis of variance and the Tukey test (alpha=0.05). The experimental group G79 without aging (7.23 +/- 2.87 MPa) presented a significantly higher mean than the other experimental groups without aging (GC: 2.81 +/- 1.5 MPa; G20: 3.38 +/- 2.21 MPa; G100: 3.96 +/- 1.57 MPa), showing no difference from G45 only (G45: 6 +/- 3.63 MPa). All specimens of the aging groups debonded during thermocycling and were considered to present zero bond strength for the statistical analyses. In conclusion, heat treatment of the metal/zirconia primer improved bond strength under the initial condition but did not promote stable bonding under the aging condition.